(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In terms of Ashtanga Yoga, it started back in the 20th century, and it was found that there were a few people who influenced it, including Krishnamacharya, Rama Mohan, Pattabhi jobs, and T.K.U Desikachar. It was Pattabhi who developed the main features of Ashtanga, but it was based on Hatha Yoga Ashtanga goal on benefits is to promote harmony within the individuals, to create a greater view of our own reality.Ashtanga Yoga is is a highly structured vinyasa-style class. There are five Ashtanga asana series and each student must master every pose of the first series before moving onto the second series. Ashtanga Yoga came to the west through students of Sri Pattabi Jois, who passed away in 2009 after establishing his yoga center in Mysore, India.